Partial Cystectomy for Primary Bladder Tumors in Contemporary Patients with Diverse Tumor Locations. Issue 1 (January 2016) - Danzig, Matthew R.; Berg, Ari R.; Ghandour, Rashed A.; Lascano, Danny; Whalen, Michael J.; Benson, Mitchell C.; DeCastro, Joel G.; McKiernan, James M.
Abstract : Introduction: : Partial cystectomy use has historically been limited by stringent selection criteria. We compared outcomes following partial cystectomy at our institution with those in other contemporary series. Also, we specifically characterized outcomes in patients with tumors in bladder locations traditionally considered unamenable to partial cystectomy. Methods: : Patients who underwent partial cystectomy for primary bladder cancer from 1990 to 2012 were identified from our database. Clinical and pathological data were reviewed. Survival analyses were performed using Kaplan‐Meier methods. Cox regression was done to identify factors associated with survival and recurrence. Results: : A total of 55 patients were included in analysis. Five‐year overall, disease specific and recurrence‐free survival was 70.3%, 77.0% and 39.4%, respectively. When controlling for clinical and pathological covariates, lymphovascular invasion predicted decreased recurrence‐free survival (HR 10.6, p = 0.025). Perioperative morbidity and mortality rates were 4% and 5%, respectively. In 8 patients (15%) trigone tumors required ureteral reimplantation. Two of the 8 patients (25%) experienced complications, including hydronephrosis and bladder neck contracture, which were treated conservatively. Cancer recurred in 2 of the 8 patients (25%) and both were treated successfully. None of the 8 patients died of bladder cancer. Conclusions: : Patients treated with partial cystectomy for primary bladder cancer had satisfactory cancer control and favorable perioperative morbidity consistent with other contemporary reports. Patients with tumors in the bladder trigone, historically considered poor candidates for partial cystectomy, also had good oncologic outcomes without significant complications related to reimplantation. Our data further support partial cystectomy in select patients with bladder cancer.